Common Neural System for Sentence and Picture Comprehension Across Languages: A Chinese–Japanese Bilingual Study - Hu, Zhengfei; Yang, Huixiang; Yang, Yuxiang; Nishida, Shuhei; Madden-Lombardi, Carol; Ventre-Dominey, Jocelyne; Dominey, Peter Ford; Ogawa, Kenji (Frontiers in Human Neuroscience, 2019)
Whereas common semantic representations for individual words across languages have been identified, a common meaning system at sentence-level based on the grammatical construction of words has not been determined. In this study, fMRI was used to investigate whether an across-language sentence comprehension system exists. Chinese–Japanese bilingual participants (n = 32) were asked to determine whether two consecutive stimuli were related (congruent) or not (incongruent) to the same event. Stimuli were displayed with three different modalities (Chinese written sentences, Japanese written sentences, and photographs). The behavioral results showed no significant difference in accuracy and response times among the three modalities. Multi-voxel pattern analysis (MVPA) of fMRI data was used to classify the semantic relationship (congruent or incongruent) across the stimulus modalities. The classifier was first trained to determine congruency within Chinese sentences, and then tested with Japanese sentences, and vice versa. A whole-brain searchlight analysis revealed significant above-chance classification accuracy across Chinese and Japanese sentences in the supramarginal gyrus (BA 40), extending into the angular gyrus (BA 39), and the opercular (BA 44) and triangular (BA 45) part of the inferior frontal gyrus in the left hemisphere (cluster-level FWE corrected p < 0.05). Significant above-chance classification accuracy was also found across Japanese sentences and photographs in the supramarginal (BA 40) and angular gyrus (BA 39). These results indicate that a common meaning system for sentence processing across languages and modalities exists, and it involves the left inferior parietal gyrus.